Social Entrepreneurship Activities in the Tourism Sector - Sirkintioğlu Yildirim, Şükran; Esen, Ülkühan Bike (IGI Global, 2021)
Social entrepreneurship is a frequently encountered and increasingly popular concept. Although there are some differences and difficulties in defining the concept, the main reason why it has become such a frequently heard concept today is the social purpose inherent in it. The ability of social entrepreneurship activities to find a place in the tourism sector will make it easier for both social entrepreneurship activities and the tourism sector to achieve their goals. Therefore, in this study, it is aimed to reveal the required fields of study by determining how the concept of social entrepreneurship is handled in the field of tourism with bibliometric analysis. In line with the purpose, 43 studies including the determined keywords were reached. When the methodologies of the articles were examined, it was concluded that empirical studies were in the majority and most of these empirical studies were prepared by using the qualitative research method.
Keywords: 8. Economic growth